Preparation Process of WC Wear-Resistant Coating on Titanium Alloys Using Electro-Spark Deposition - Haodong Liu; Liuqing Huang; Dongsheng Wang; Changjun Chen; Aiyong Cui; Shikang Dong; Zhiwei Duan (Archives of Metallurgy and Materials)
Due to their excellent corrosion resistance and high specific strength, Ti alloys are widely used in shipboard aircraft structures. However, their low wear resistance limits further applications. In this study, wear-resistant tungsten carbide (WC) coatings were applied to TC4 alloy using electro-spark deposition (ESD), and the processing parameters were optimized through orthogonal testing. The effects of ESD processing parameters on the surface morphology of the wear-resistant WC coating were also investigated. The results showed that output voltage, deposition frequency, and electrode speed significantly influenced coating morphology. A relatively flat and uniform coating on the titanium alloy surface was achieved with WC coatings prepared under an output voltage of 120 V, deposition frequency of 120 Hz, and electrode speed of 350 r.